Scanning electron microscopy and calcification in amelogenesis imperfecta in anterior and posterior human teeth. - Sánchez Quevedo, M. C. (2001)
Teeth fragments from members of a family clinically and genetically diagnosed as having amelogenesis imperfecta were studied by scanning electron microscopy and X-ray microprobe analysis to establish the morphological patterns and the quantitative concentration of calcium in the enamel of anterior (canine, incisor) and posterior (premolar and molar) teeth. The prism patterns in the enamel of teeth from both regions were parallel or irregularly decussate, with occasional filamentous prisms accompanied by small, irregularly rounded formations. Prismless enamel showed the R- and P-type patterns. Calcium levels in enamel of amelogenesis imperfecta and control teeth differed significantly between anterior and posterior teeth, indicating that the factors that influence normal mineralization in different regions of the dental arch are not altered in the process of arnelogenesis imperfecta.